Study of the deficit in planning abilities of adults with Prader-Willi Syndrome. (October 2021) - Estival, Séverine; Chevalère, Johann; Laurier, Virginie; Mourre, Fabien; Tricot, Julie; Postal, Virginie
Highlights: Prader-Willi Syndrome is associated with intellectual disability and executive deficits. Deficits in planning capacities lead to poor personal autonomy. Intellectual level is linked to planning deficits in Prader-Willi Syndrome. Better knowledge on planning deficits in Prader-Willi Syndrome helps identify rehabilitation axes. Abstract: Background: Prader-Willi syndrome (PWS) is a complex developmental genetic disorder associated with intellectual disability and deficits in executive functions which result in disorganisation and poor personal autonomy. Aims: This study aimed to determine impairments in planning skills of adults with PWS, in relation with their intellectual disabilities, as well as the influence of food compulsions on their performance. Methods and procedures: A modified version of the Zoo Map from the Behavioural Assessment of the Dysexecutive Syndrome was used in three groups: a group of adults with PWS in comparison with two groups both matched on chronological age, one with typical development (TD) and one with intellectual disability (ID). Outcomes and results: Compared to TD adults, both adults with PWS and ID showed increased planning time and lower raw scores on the planning task. The execution time and the number of errors were higher in the PWS group compared to the comparison groups. All three groups performed worse in the non-food condition only for number of errors and raw score. Conclusions and implications: Planning abilities were impaired in PWS adults. Results also showed that intellectual level plays a role in participants' performance. These findings are essential to understand the difficulties of people with PWS daily life.